Principal Management In Realizing Khalifatullah-Based Student Character Education At SMK PGRI 2 Pasuruan - Dewi, Adinda Sitra Kusuma; Umro, Jakaria (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
The purpose of this research is to describe how the principal manages character education based on khalifatullah and to identify the supporting and inhibiting factors. The research method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research findings indicate that the principal's management in implementing character education based on khalifatullah is carried out through three main stages, namely planning, implementation, and supervision and evaluation. The planning stage includes the preparation of programs that integrate religious values, responsibility, and role models. The implementation stage is realized through habituation activities such as morning prayers accompanied by readings from the Qur'an and sholawat Busyro, mandatory literacy of reading the Qur'an for students, and the implementation of congregational Dhuhr prayers. Supervision is carried out through class reports, teacher evaluations, and teacher council forums. Supporting factors for this management include a religious school environment, exemplary teachers and school principals, and structured programs. Meanwhile, the obstacles include low student discipline, teachers' tight schedules, lack of parental support, and the influence of the school's external environment. Based on these results, it can be concluded that the principal's management plays an important role in realizing the character of students based on the concept of being a caliph, and its success is greatly influenced by the synergy between the school, family, and the students' social environment.